HISTORY OF THE DEVELOPMENT OF MEDIASAVODKHANATE IN STATE BODIES - Mansur Yunusov (Galaxy International Interdisciplinary Research Journal, 2024)
This purpose is the history of the development of mediasavodkhanate in the state body and the importance of today scientific and practical activities the main materials have been studied and recommendations of the competition for public services have been developed.